1954
DOI: 10.1021/jo01375a014
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophenoxyethoxyethanols From Polychlorobenzenes

Abstract: There are numerous references in the literature to the synthesis of various halophenoxyethanols, or ethylene glycol halophenyl ethers, by the reaction of sodium halophenates with ethylene chlorohydrin (1-4). The corresponding esters have also been reported, including acetates, methacrylates, crotonates, maleates, and cinnamates (4-7).Another procedure used less frequently for the synthesis of halophenoxyethanols involves the condensation of halophenols with ethylene oxide (3, 5). By this method 2-(pentachlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1974
1974

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In other cases, pentachlorophenol ethers are obtained; for example, boiling potassium hydroxide in ethanol gives a 95% yield of the ethyl ether [74]. Similar results are obtained with sodium hydroxide in triethyleneglycol at 200 0 [230] or in methanol at 120° [186] giving, respectively, the hydroxyphenol ether and pentachloroanisole. It has recently been found that when the reaction with sodium hydroxide is carried out in dimethylsulphoxide (DMSO) at 110-120° a 97% of pentachlorophenol is obtained [231].…”
Section: (H) Other Nucleophilic Substitutionsmentioning
confidence: 54%
“…In other cases, pentachlorophenol ethers are obtained; for example, boiling potassium hydroxide in ethanol gives a 95% yield of the ethyl ether [74]. Similar results are obtained with sodium hydroxide in triethyleneglycol at 200 0 [230] or in methanol at 120° [186] giving, respectively, the hydroxyphenol ether and pentachloroanisole. It has recently been found that when the reaction with sodium hydroxide is carried out in dimethylsulphoxide (DMSO) at 110-120° a 97% of pentachlorophenol is obtained [231].…”
Section: (H) Other Nucleophilic Substitutionsmentioning
confidence: 54%
“…The preparation and study of this functional group has been gaining interest because of its application as a condensing agent. Substituted carbo diimides have been applied to the synthesis of amidines, anhydrides, amides, carboxylic acids, sulfonic acids, esters, and other functional groups [2]. Other reviews are also worth considering [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The first review of carbodiimides was published in 1953 [la], and a more recent one appeared in 1967 [lb]. The synthesis of peptide linkages with the aid of carbodiimides has also attracted a great amount of interest [2]. Substituted carbo diimides have been applied to the synthesis of amidines, anhydrides, amides, carboxylic acids, sulfonic acids, esters, and other functional groups [2].…”
Section: Introductionmentioning
confidence: 99%